IMPROVING STUDENTS’RESEARCH COMPETENCE IN TEACHING THE KAZAKH LANGUAGE - Ибрагимова, Эльмира; KHEGAY, N. (Pedagogy and Psychology, 2024)
The article discusses the enhancement of students’ research competence within the context of teaching the Kazakh language. Developing learners’ research skills is becoming a significant factor in higher education system. This research seeks to undertake a detailed examination of students’ attitudes toward the Kazakh language, identify existing obstacles, and design effective strategies to assist the development of research competency within the context of Kazakh language and culture studies. This study examines both foreign and local studies to provide a methodology for teaching languages and culture. It also attempts to promote a successful integration of research approaches into the learning process for Kazakh language acquisition. This study paper applies a qualitative method, using semi-structured interviews, to collect thorough data on students’ opinions and experiences with developing research abilities while learning the Kazakh language. The methodology intends to explore the many features of competence, language acquisition issues, and the significance of research activities in improving students’ language proficiency.